Impacts of ontogenetic dietary shifts on the food-transmitted intestinal parasite communities of two lake salmonids. (August 2020) - Prati, Sebastian; Henriksen, Eirik Haugstvedt; Knudsen, Rune; Amundsen, Per-Arne
Abstract: Ontogenetic dietary shifts are common in fish and often impact trophically transmitted parasite communities. How parasite species composition and relative abundances change among size classes, and at what rate these changes occur, is rarely examined. Hosts with a broad trophic niche are potentially exposed to a large variety of parasite species. The degree of ontogenetic changes in parasite species composition versus changes in parasite abundance should suggestively differ between thropically generalist and specialist host species. In the present study, we explore ontogenetic dietary shifts and their impact on species composition and relative abundance of intestinal parasites in two sympatric salmonid fish species, Arctic charr ( Salvelinus alpinus ) and brown trout ( Salmo trutta ) caught in the littoral habitat of a subarctic lake. Our results highlight a close interplay between ontogenetic dietary niche shifts and alterations in the acquisition of trophically transmitted parasites, leading to host-specific differences in the component community of parasites. Ontogenetic changes in the intestinal parasite community related to dietary niche shifts were distinct but less pronounced in Arctic charr than in brown trout due to a broader and more consistent dietary niche of the former and an ontogenetic shift toward piscivory in the latter. At the component community level, changes in parasite assemblages of both host species were driven by a faster increase in the heterogeneity of parasite relative abundance than in the compositional heterogeneity, a pattern that partly may be related to a rather species-poor parasite community of this subarctic study system. Separating compositional heterogeneity from heterogeneity in relative parasite abundance is important to understand how size-dependent variability shapes parasite communities of host populations. Graphical abstract: Image 1 Highlights: Ontogenetic dietary niche shifts generated host-specific differences in the component community of parasites. Ontogenetic changes in the intestinal parasite community were less pronounced in Arctic charr than in brown trout. Heterogeneity of parasite relative abundance increased faster than the compositional heterogeneity.